HUBUNGAN USIA IBU HAMIL, PARITAS DAN KUNJUNGAN ASUHAN ANTENATAL DENGAN KEJADIAN PREEKLAMPSIA - Laura, Cindy; S.P. Hutasoit, Eka; C. Eyanoer, Putri (Jurnal Kedokteran Methodist, 2021)
Background: Preeclampsia is hypertension with blood pressure ≥ 140/90 mmHg or hypertension that happens following 20 weeks of gestation. Clinical symptoms of preeclampsia are divided into preeclampsia without severe symptoms and severe preeclampsia. Risk factors that can cause preeclampsia are maternal age, obesity, parity, multiple pregnancies, antenatal care visits, diabetes and or then again have experienced preeclampsia in past pregnancies. Method : This study uses a literature review study. The journals used are publications over the most recent five years and full text articles and the languages ​​used are Indonesian and English. Result : Based on a literature review study found as many as 20 journals related to the relationship between maternal age, parity and antenatal care visits with the incidence of preeclampsia. Conclusion: There is a relationship between maternal age, parity and antenatal care visits with the incidence of preeclampsia.